2013
DOI: 10.1007/s13593-013-0147-8
|View full text |Cite
|
Sign up to set email alerts
|

Agrobiodiversity for food security, health and income

Abstract: By the year 2050, agriculture will have to provide the food and nutrition requirements of some 9 billion people. Moreover, to maintain that level of productivity indefinitely it must do so using environmentally sustainable production systems. This task will be profoundly complicated by the effects of climate change, increasing competition for water resources and loss of productive lands. Agricultural production methods will also need to recognize and accommodate ongoing rural to urban migration and address a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(145 citation statements)
references
References 98 publications
(88 reference statements)
1
112
0
12
Order By: Relevance
“…In contrast to the above-mentioned major staple crops, underutilized, undervalued or neglected crops-also branded development opportunity crops (DOCs) [27]-are categorized in this article as -minor crops‖ that are already cultivated, but are underutilized regionally or globally given their still relatively low global production and market value [20,28,29]. Some of these crop species may be widely distributed globally, but are restricted to a more local production and consumption system.…”
Section: The Importance Of Underutilized Traditional Crops For Sustaimentioning
confidence: 99%
“…In contrast to the above-mentioned major staple crops, underutilized, undervalued or neglected crops-also branded development opportunity crops (DOCs) [27]-are categorized in this article as -minor crops‖ that are already cultivated, but are underutilized regionally or globally given their still relatively low global production and market value [20,28,29]. Some of these crop species may be widely distributed globally, but are restricted to a more local production and consumption system.…”
Section: The Importance Of Underutilized Traditional Crops For Sustaimentioning
confidence: 99%
“…Diets of developing countries are frequently deficient in macronutrients (protein, carbohydrates and fat), micronutrients or both (Brabin & Coulter, 2003). Although, in common with other legumes, Bambara is deficient in sulphur-containing amino acids (Azam-Ali et al, 2001;Mayes et al, 2012), some genotypes contain higher amounts of methionine and lysine than is found in other legumes (National Research Council, 2006;Kahane et al, 2013). Bambara groundnut is known to come in a variety of colors.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that only 30 or so plant species feed the world today has been highly stigmatized in recent years: the narrowing of our food security basket makes food systems more vulnerable to shocks of different nature, which is particularly severe for the poor whose livelihood options are dramatically reduced [2,3].…”
Section: Introductionmentioning
confidence: 99%